Applying an Electronic Inquiry-Based Learning Environment to Promote Preparatory-Stage Students' EFL Fluency - Ahmed Abdel Rahman; Asmaa Gheith; Badr Abdel- Kafi (Port Said Journal of Educational Research, 2024)
The current study seeks to determine how preparatory-stage students develop their EFL fluency resulting from exposure to an electronic program based on the inquiry-based learning (IBL) method. The researcher made use of two social media platforms: Telegram and Skype. The participants were 15 preparatory-stage students in a governmental school, Qena, who were chosen at random by the researcher. Before conducting the current study, a pilot study was conducted in the form of an interview with a pre-posttest to assess their EFL fluency ability. There are ten EFL fluency components in the electronic program. The information is analyzed quantitatively. The Wilcoxon test was used to calculate the extent of the effect of the proposed program on increasing the research participants' EFL fluency. The results showed that the study participants' overall mean scores on the post-administration of the test were higher than their total mean scores on the pre-administration of the test. The researcher found that teachers should employ a variety of e inquiry-based activities to aid students improve their EFL fluency and that more time should be given so that students may put their information into practice, think about it, and applying it to different real-world situations. As a result, the proposed  program demonstrated that it had a very substantial effect on developing EFL fluency in preparatory-stage students.